2017
DOI: 10.1007/s10067-017-3868-2
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic features in patients with ANCA-associated vasculitis within 3 months before and after diagnosis

Abstract: We investigated the all-inclusive echocardiographic features in patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) within 3 months before and after diagnosis. We reviewed the medical records of 89 AAV patients taking echocardiography and 35 age- and gender-matched controls. We collected clinical and laboratory data and echocardiographic results. We compared the variables between patients with AAV of each variant and controls and among those with microscopic polyangiitis (MPA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Therefore, we suspected that the occurrence of STEMI complications in patients was related to mCRP [12]. AAV exhibits various echocardiographic characteristics, such as decreased systolic function, increased diastolic dysfunction, and pulmonary hypertension at the time of diagnosis [60]. The current study focused on cardiovascular disease in patients with AAV, which reflected the clinical examination of cardiovascular function by echocardiography.…”
Section: Table 2 Comparison Of the Relationship Between Clinical Indimentioning
confidence: 96%
“…Therefore, we suspected that the occurrence of STEMI complications in patients was related to mCRP [12]. AAV exhibits various echocardiographic characteristics, such as decreased systolic function, increased diastolic dysfunction, and pulmonary hypertension at the time of diagnosis [60]. The current study focused on cardiovascular disease in patients with AAV, which reflected the clinical examination of cardiovascular function by echocardiography.…”
Section: Table 2 Comparison Of the Relationship Between Clinical Indimentioning
confidence: 96%
“…Furthermore, measuring right ventricular systolic pressure (RVSP), which can estimate the presence of pulmonary arterial hypertension, the authors indicated that MPA and EGPA patients, but not GPA patients, showed enhanced RVSP than controls. However, there were no significant differences in LVEF, E/E' ratio and RVSP among patients with MPA, GPA and EGPA 88. Physicians should be encouraged to perform echocardiography within 3 months after diagnosis of AAV.…”
Section: Othersmentioning
confidence: 86%
“…Initial involvement of the heart was reported to be related to poor prognosis 3087. Recently, Ahn, et al88 reported the results of echocardiography performed 3 months before and after diagnosis of AAV in 89 Korean patients. They compared echocardiographic results in AAV patients with those in age- and gender-matched healthy controls.…”
Section: Othersmentioning
confidence: 99%
“…Therefore, we suspected that the occurrence of STEMI complications in patients was related to mCRP [12]. AAV exhibits various echocardiographic characteristics, such as decreased systolic function, increased diastolic dysfunction, and pulmonary hypertension at the time of diagnosis [60]. The current study focused on cardiovascular disease in patients with AAV, which re ected the clinical examination of cardiovascular function by echocardiography.…”
Section: Discussionmentioning
confidence: 98%